KEANEKARAGAMAN JENIS BURUNG DI KEBUN CAMPURAN - Hadinoto, hadinoto; Suhesti, Eni (Fakultas Kehutanan Universitas Lancang Kuning, 2021)
Birds are one of the ecosystem components that have an important role in supporting the life cycle of organisms. The research objectives were to calculate the diversity of bird species and identify sources of bird feed in mixed gardens. Bird data were analyzed using Species Diversity Index, Species Richness Index, Species Abundance Index, dominance analysis, bird distribution analysis and species encounter level analysis, for vegetation analyzed based on the type and part eaten by the birds. In the mixed garden of Pandau Jaya Village, 27 species of birds were found consisting of 15 families. The types of birds that were frequently present were the Cucak Kutilang (Pycnonotus aurigaster) with 44 individuals and the Perkutut Jawa (Geopelia striata) with 37 individuals. Bird species diversity (H) in mixed gardens was relatively moderate with a value of 2.90, the Evenness Index (E) of 0.88 and the Reachennes Index (R) of 4.40. Vegetation types as a source of food: Mahogany, Jengkol, Jackfruit, Jambu Air, Acacia mangium, Rubber, Matoa, Salam, Angsana, Mango, Breadfruit, Rambutan, Longan, Starfruit, Sengon, Kersen, Lamtoro, Beringin, Ketapang, Mahang, Palm Oil , Coconut, Areca, Palm, Cassava, Sweet Potatoes, Corn, Taro, Eggplant, Chili, Tekokak, Lengkuas, Sugarcane, Long Beans, Banana, Papaya, Flowers,Grasses.